2009
DOI: 10.2320/matertrans.m2009289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermetallic Compound Layer on Tensile Strength of Dissimilar Friction-Stir Weld of a High Strength Mg Alloy and Al Alloy

Abstract: The friction stir weldability of a fine-grained high strength AZ31B magnesium alloy to A5083 Al alloy was evaluated at various welding conditions, by using a tool with shoulder diameter of 15 mm, pin diameter of 5 mm and pin length of 3.9 mm. A square butt dissimilar joint without any defect was obtained at the condition of welding speed 100 mm/min, tool rotating speed 500 rpm and offset 0 mm. Higher or lower welding speeds or rotating speeds led to either the formation of defect or lack of bonding in the join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 18 publications
2
56
1
1
Order By: Relevance
“…While the yield stress and ultimate tensile strength of A3 sample are just slightly smaller than the ones of A1, elongations up to initial and overall fractures are strongly decreased to 0.150 and 0.215, respectively, with the increase of annealing time from 1 to 3 h at 300 1C. This is meeting the expectations as the profound growth of the brittle intermetallic compounds by over-annealing do harmful effect upon the mechanical interlock at the interface [30,31]. However, this does not directly mean that there is not a variety of possibilities for improving mechanical properties of clad metals given by post-annealing which somewhat induces the generation of IMCs at interface.…”
Section: Uniaxial Tensile Properties Of Sts-al-mg Three-ply Compositessupporting
confidence: 68%
“…While the yield stress and ultimate tensile strength of A3 sample are just slightly smaller than the ones of A1, elongations up to initial and overall fractures are strongly decreased to 0.150 and 0.215, respectively, with the increase of annealing time from 1 to 3 h at 300 1C. This is meeting the expectations as the profound growth of the brittle intermetallic compounds by over-annealing do harmful effect upon the mechanical interlock at the interface [30,31]. However, this does not directly mean that there is not a variety of possibilities for improving mechanical properties of clad metals given by post-annealing which somewhat induces the generation of IMCs at interface.…”
Section: Uniaxial Tensile Properties Of Sts-al-mg Three-ply Compositessupporting
confidence: 68%
“…Taking the values of YS and UTS calculated on the basis of ROM into consideration, the results provide strong evidence that experimentally measured tensile strengths for the 3-ply sheet fabricated by roll bonding adopted in this study are obviously improved, regardless of annealing treatment, which is primarily attributed to the adequate interfacial strengthening. However, it was also found that the difference between the experimentally determined and ROM-based tensile strength decreased upon increasing annealing time, which implies that the profound growth of the brittle IMCs at interfaces by overannealing have a detrimental effect on the mechanical interlocking at the interface [24,25]. Unlike tensile strength, an estimate of homogeneous composite strain cannot be supported by means of ROM theory [26].…”
Section: Uniaxial Tensile Properties Of Sts-al-mg Three-ply Compositesmentioning
confidence: 87%
“…One proposed method is to use friction stir welding. This process reaches lower temperatures, and thus may help minimize intermetallic formation [6]. Friction stir welding of magnesium and aluminum has been shown to be possible, but it was found that the hardness across the joint became twice that of the base materials [7].…”
Section: Introductionmentioning
confidence: 98%